Civil Society Organizations Against Terrorism : case studies from Asia - Gunaratna, Rohan, 1961-; Aslam, Mohd Mizan (London: New York: Routledge, Taylor & Francis, 2021)
"With recent changes in social and political landscapes around the world the focus of preventive counter-terrorism has shifted in many places from government to civil society. The contributors analyse the different approaches of Civil Society Organisations in preventing and countering violent extremism in various countries in South and Southeast Asia. The cases examined include, Malaysia, Indonesia, Myanmar, Sri Lanka and Bangladesh. The key emphasis is on understanding the contest within which each example was initiated, and the factors that determined their relative success or failure. The evidence from these cases suggests that much can be achieved through empowering communities to engage in aiding both the indoctrinated and those who pose the greatest risk of radicalisation. A valuable contribution to the literature on preventing and countering violent extremism"
Includes bibliographical references and index.
Keywords: Terrorism -- Southeast Asia -- Prevention; Terrorism -- South Asia -- Prevention; Radicalism -- Southeast Asia; Radicalism -- South Asia; National security -- Southeast Asia; National security -- South Asia